Employee Happiness Measurement System on Assigned Task in Agile Process - Tongpaeng, Yootthapong; Sureephong, Pradorn; Wadwongyod, Piraya (2022 25th International Symposium on Wireless Personal Multimedia Communications (WPMC), 2022)
In organizations driven by technology, amidst the digital age, an agile working policy is the most utilized policy as it meets the demand of the current day's work style and is suitable for organizations that are ready for changes. However, it requires standardized and efficient internal management. A project management tool is one of the tools that help employees in an organization support their agile work styles by allowing for smooth collaboration and progress tracking. Furthermore, such organizations prioritize happiness at work. However, project management tools have yet to be suited for managing the happiness of work and workload systematically. According to the study, certain departments in the organization found themselves to have many daily tasks. Department heads or staff were incapable of seeing the overview or plan or distributing workload evenly. This study introduced a combination of employee workload and happiness management tools and project management tools to create appropriate workload planning and focus more on workload flexibility or happiness at work in the future strategically. Additionally, this tool helps decrease excessive daily workload and time spent on project management. Furthermore, happiness from each individual in the organization; executive, human resources, and head of the department; and executive will reduce work stress, which increases the happiness of staff within departments and allows better adaptation to agile working. and also help gain employee happiness levels in the future.